The Influence of Bank Reputation and Products on Savings Decisions: Case Study from PT. Bank Muamalat Indonesia Tbk. Mamuju Branch, Indonesia - Yolanda, Khaeronisa Milenya; Fajariani, Nur; Asia, Nur (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to determine the effect of Reputation variables and Bank Products on Saving Decisions at PT. Bank Muamalat Indonesia Tbk. Mamuju Branch. The research method used is to use quantitative methods with primary data using a questionnaire. Respondents in the study were all people who saved at PT Bank Muamalat Tbk Mamuju Branch, the sample used accidental sampling technique with a sample size of 30 respondents. The formula in this study uses validity test, reliability test, multiple linear regression, t test, and F test. The results in this study indicate that bank reputation and products have a positive and significant effect partially on saving decisions at PT. Bank Muamalat Indonesia Tbk. Mamuju Branch. Reputation and bank products simultaneously have a significant effect on saving decisions at PT. Bank Muamalat Indonesia Tbk. Mamuju Branch.